Advances in Systems, Control and Automation ETAEERE-2016 - Konkani, Avinash; Bera, Rabindranath; Paul, Samrat; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book comprises the select proceedings of the ETAEERE 2016 conference. The book aims to shed light on different systems or machines along with their complex operation, behaviors, and linear-nonlinear relationship in different environments. It covers problems of multivariable control systems and provides the necessary background for performing research in the field of control and automation. Aimed at helping readers understand the classical and modern design of different intelligent automated systems, the book presents coverage on the control of linear and nonlinear systems, intelligent systems, stochastic control, knowledge-based systems applications, fault diagnosis and tolerant control, real-time control applications, etc. The contents of this volume will prove useful to researchers and professionals alike.
Evaluation of Harmonics and THD in5-phase Inverter constructed withHigh-pass filterby Matlab simulation -- Theoretical analysis of the electrical and Optical properties of ZnS -- Hybrid Fuzzy Recommendation System for Enhanced E-Learning -- Tension Controllers for a Strip Tension Levelling Line -- Linear Synchronous Reluctance Motor  -  A Comprehensive Review -- Mitigation of Circulating Current in Diode Clamped MLI fed Induction Motor Drive using Carrier Shifting Algorithms -- A comparative analysis of determination of design parameters of Boost and Buck-Boost converter using Artificial Intelligence -- Optimization of induction motor using genetic algorithm and GUI of optimal induction motor design in MATLAB -- High Response Photon-Counting for phase fraction measurement using Compact RIO with FPGA -- Numerical Stress Analysis of Artificial Femur Bone -- Investigation of Perylene as a converter material for Fast Neutron Detection and Spectroscopy using GEANT4 Monte Carlo Simulations -- DesignAnd Analysis of A Permanent Magnet DC Motor -- Sleep stage classification using s-transform based spectral energy feature -- Fundamental Concepts of Neural Networks and Deep Learning of Different Techniques to Classify the Handwritten Digits -- Tuning PID Controller for inverted pendulum Using Genetic Algorithm -- A New Development Methodology for High Precision ISP -- Design of Spectrum Sensing System -- Experimental/Simulation study to check significance of proximity effect -- Denoising of MRI Images using Curvelet Transform -- Comparative analysis of membrane potential of bone cell and its abnormalities -- Electro Optically Tunable Switching Action Enhanced by Long Range Surface Plasmon.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Electric power production; Signal processing; Machinery; Multibody Systems and Mechanical Vibrations; Electrical Power Engineering; Signal, Speech and Image Processing; Machinery and Machine Elements